METHOD FOR DETERMINATION OF FOCAL PLANE LOCATION OF FOCUSING COMPONENTS - A. I. Ivashko; V. E. Kisel; N. V. Kuleshov (Приборы и методы измерений)
Mass-production of different laser systems often requires utilization of the focal spot size method for determination of output laser beam spatial characteristics. The main challenge of this method is high accuracy maintenance of a CCD camera beam profiler in the collecting lens focal plane. The aim of our work is development of new method for placing of photodetector array in the collecting lens focal plane with high accuracy.Proposed technique is based on focusing of several parallel laser beams. Determination of the focal plane position requires only longitudinal translation of the CCD-camera to find a point of laser beams intersection. Continuous-wave (CW) diode-pumped laser emitting in the spectral region near 1μm was created to satisfy the requirements of the developed technique. Designed microchip laser generates two stigmatic Gaussian beams with automatically parallel beam axes due to independent pumping of different areas of the one microchip crystal having the same cavity mirrors.It was theoretically demonstrated that developed method provides possibility of the lenses focal plane determination with 1 % accuracy. The microchip laser generates two parallel Gaussian beams with divergence of about 10 mrad. Laser output power can be varied in the range of 0.1–1.5 W by changing the pumping laser diode electrical current. The distance between two beam axes can be changed in the range of 0.5–5.0 mm.We have proposed method for determination of positive lens focal plane location by using of CCDcamera and two laser beams with parallel axes without utilization of additional optical devices. We have developed CW longitudinally diode pumped microchip laser emitting in the 1-μm spectral region that can be used in the measuring instrument that doesn’t require precision mechanical components for determination of focal plane location with 1 % accuracy. The overall dimensions of laser head was 70 × 40 × 40 mm3 and maximum power consumption was 7W per one laser beam.